GEPRO: Gene Expression Profiler for DNA microarray data - Kim, Beob G.; Lindemann, Merlin D; Bridges, Phillip J.; Ko, CheMyong (Revista Colombiana de Ciencias Pecuarias, 2009)
Summary The DNA microarray technology has been widely employed in recent biological research. However, the unprecedented large amount of data produced by the technology has presented inevitable challenges to biological scientists, forcing individual researchers to take extensive training or rely on database specialists for the use of the data. Microsoft Excel® has a number of convenient functions and may be the most widely used spreadsheet package for data storage and manipulation. Therefore, we developed a userfriendly, Excel spreadsheet-based microarray data-managing program. The program, gene expression profiler (GEPRO), is designed to facilitate organizing miocroarray data, performing statistical analysis, and displaying the results. Using GEPRO's filtering and sorting capabilities, a user can easily identify differentially expressed genes, display the expression profiles of the genes of interest, and present and save the analyzed data in a user-defined way. The versatility and utility of GEPRO should enable bench work researchers to maximize the use of their microarray data. The GEPRO is freely available for noncommercial users at http://www.mc.uky.edu/cls/ko/gepro1.html.